Cocktail of Astragalus Membranaceus and Radix Trichosanthis Suppresses Melanoma Tumor Growth and Cell Migration Through Regulation of Akt-Related Signaling Pathway - Zhang, Qiuyan; Gao, Lei; Huang, Songli; Liang, Yuxi; Hu, Jingyan; Zhang, Yuan; Wei, Shengli; Hu, Xiuhua (Frontiers in Pharmacology, 2022)
Background: Malignant melanoma has high morbidity and mortality and limited treatment options. Traditional Chinese medicine has great potential in the clinical therapy of cancer, and the theory of compatibility is one core content of Chinese medical theory. Astragalus Membranaceus and Radix Trichosanthis are clinically effective for the treatment of various cancers. Methods: We verified the effects of AMD, RTD, and their “cocktail” on melanoma model in vitro and in vivo and the mechanism of its effect on the Akt-related signaling pathway by network pharmacology, MTT, flow cytometry, LDH, SOD, MDA assay, and Western blot. Results: The network pharmacology analysis indicated that the PI3K-Akt pathway plays a crucial role in the treatment of malignant melanoma with these two herbs. In addition, AMD, RTD, and their “cocktail” could inhibit the proliferation of A375 cells by reducing the survival rate in a concentration-dependent manner and by regulating the cell cycle, and the compatibility of two herbs also could inhibit melanoma growth. They could, respectively, induce apoptosis and inhibit migration by affecting the expression of Bcl-2, Bax, p53, snail, E-cadherin, and N-cadherin. Furthermore, LDH activity was decreased, while SOD increased and MDA reduced. The factors of the Akt-related signaling pathway, Akt and p-Akt, were decreased. Conclusion: This study showed that AMD, RTD, and their “cocktail” could regulate cell proliferation, apoptosis, and metastasis in A375 cells through the suppression of the Akt-related signaling pathway, and the “cocktail” groups had detoxification and additive effects. The best compatibility of the two herbs also can inhibit tumor growth and metastasis in vivo.